ANALISIS DAMPAK OTONOMI DAERAH TERHADAP STRATEGI PENGEMBANGAN PERGURUAN TINGGI SWASTA (PTS) DI KABUPATEN SLEMAN - Badrudin, Rudy (Universitas Muhammdaiyah Surakarta, 2008)
This research analyze the effect of regional autonomy to the interest of collegeâs student candidate to continue studying in Sleman Regency which researchâs samples for major programâs chosen was Accounting, Management, and Economics in UII, UAJY, UPNVY, and STIE YKPN. The result of research with Boston Consulting Group (BCG) Matrix shows that each major program in four universities and college was in different quadrant. Therefore, each university and college has to choose different development strategic specifically even for each major programs in each university and college, so that the major programs in four universities and college in Sleman Regency could grow and rise.